PENGARUH MEDIA PEMBELAJARAN BERBASIS INFORMATION TECHNOLOGY (IT) GOOGLE CLASSROOM DAN ZOOM TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN JASMANI STKIP SEBELAS APRIL SUMEDANG - Zaenal Arifin (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
This research aims to find out the influence of Information Technology (IT)-based learning media between classes that learn using Google Classroom media and classes that learn by using Zoom media on student learning motivation. The problem formulation in research is: (1) whether there is an influence of Google Classroom learning media on the motivation of learning students of Physical Education STKIP Sebelas April Sumedang (2) whether there is an influence of Zoom learning media on the motivation of learning students of Physical Education STKIP Sebelas April Sumedang. (3) whether there is a significant difference in influence between Google Classroom and Zoom learning media on the learning motivation of STKIP Physical Education students Sebelas April Sumedang. This research uses quasi experiment methods, with quasi experimental design research design and uses two group pretest-posttest design. The results showed that (1) there is an influence of Google Classroom learning media on the learning motivation of STKIP Physical Education students Sebelas April Sumedang. (2) There is the influence of Zoom learning media on the motivation of learning students of Physical Education STKIP Sebelas April Sumedang. Between the initial test and the final test it has an effect on motivation on the Zoom group. (3) There is a significant difference in influence between Google Classroom and Zoom learning media on the learning motivation of STKIP Physical Education students Sebelas April Sumedang. The consistent value of google classroom group motivation is greater than zoom group.